The role of platelets in inflammation and immunity - S. P. Sviridova; O. V. Somonova; Sh. R. Kashiya; O. A. Obukhova; A. V. Sotnikov (Исследования и практика в медицине, 2018)
In recent decades, significant progress has been made in understanding the mechanisms of platelet function and platelet hemostasis correction. Platelets are considered as the most important participants of both normal, and pathological thrombotic process characteristic of the most diﬀerent diseases and states. In the present review pathophysiological mechanisms of platelet synthesis of various mediators with paracrine eﬀects, which can influence the function of other cells, are consecrated. The physiology of platelets was considered in detail. The leading role of platelets in pathogenesis of the majority of diseases of cardiovascular system as modulators of inflammatory reactions of the immune response which are considered as the leading mechanism of development of atherosclerosis was shown. The ability of platelets to encode inflammatory proteins allowing them to influence adaptive immunity functions was discussed. The role of platelets as a key component of the innate immune system was presented, which is confirmed by the presence of Tolllike receptors (TLR) and glycoproteins, such as integrin αIIbβ3, glycoprotein Ib-IX and FcγRIIa, involved in interaction with bacterial cells. The pathogenesis of the formation of platelet-leukocyte aggregates due to the rapid reversible interaction of P-selectin (CD62P) on the platelet surface with ligand-1 glycoprotein P-selectin (PSGL-1) on the plasma of leukocytes and the mechanism of extracellular neutrophil traps (NETs), as well as the influence of platelets on the function of lymphocytes was presented. The role of platelets in cancer progression, metastasis and thrombosis is considered, and the interrelation of thrombosis and metastasis in malignant diseases was analyzed. The eﬃciency of the use of antithrombotic drugs in the prevention of thrombosis and, as a consequence, in the prevention of cardiovascular diseases and cancer was discussed.